Gaṇamādhyame Bāṃlādeśera muktiyuddha = Media and the liberation war of Bangladesh. - Mamoon, Muntassir, 1951-; Centre for Bnagladesh Studies (Dhaka : Centre for Bnagladesh Studies, 2002)
Articles, reports, and cartoons collected from various newspapers and news magazines on the 1971 liberation war of Bangladesh.
[v.] 1. Kārṭuna / saṃkalana o sampādanā, Riẏāja Āhameda = Cartoons / compiled and edited by Reaz Ahmed -- v. 2. Selections from the Frontier / compiled and edited by Muntassir Mamoon -- 3. khaṇḍa. Mujibanagara, muktāñcala o abaruddha Bāṃlādeśa theke prakāśita patrapatrikā / saṃkalana o sampādanā, Hāsin̄a Āhameda -- v. 4. Mujibanagara, muktāñcala, abaruddha Bāṃlādeśa theke prakāśita patrapatrikā / saṃkalana o sampādanā, Hāsin̄a Āhameda -- v. 5. Mujibanagara, muktāñcala o abaruddha Bāṃlādeśa theke prakāśita patrapatrikā / saṃkalana o sampādanā, Hāsinā Āhameda -- v. 6. Dainika Ānandabājāra patrikā theke saṃkalana -- v. 7. Dainika Ānandabājāra patrikā theke saṃkalana / saṃkalana o sampādanā, Munatāsīra Māmuna -- v. 8. Dainika Ānandabājāra patrikā theke saṃkalana -- v. 9. Mujibanagara, muktāñcala, o abaruddha Bāṃlādeśa theke prakāśita patrapatrikā / saṃkalana o samp̄adanā, Hāsinā Āhameda
Bengali and English; v. 2 in English.
Vol. 4-9 published by Ananyā, Dhaka.
"Gaṇamādhyame Bāṃlādeśera muktiyuddha granthamālā"--V. 1, p. 4.
Includes bibliographical references and index.
Keywords: India-Pakistan Conflict, 1971 -- Mass media and the conflict; Bangladesh -- History -- Revolution, 1971.; Bangladesh -- History -- Revolution, 1971 -- Mass media and the revolution